(untitled) - Watrall, Ethan (Indianapolis, 2006)
Savvy -- n. Practical know-how. Build your skills and make an impact on your Web site in a flash with this revamped update to the top-selling Flash MX 2004 Savvy.
Keywords: Computer animation,Flash (Computer file),Hình ảnh động trên máy tính,Flash (Chương trình máy tính)